Personal and professional use of menopausal hormone therapy among gynecologists: A multinational study (REDLINC VII). (May 2016) - Danckers, Luis; Blümel, Juan E.; Witis, Silvina; Vallejo, María S.; Tserotas, Konstantino; Sánchez, Hugo; Salinas, Carlos; Saavedra, Javier; Rojas, José A.; Onatra, William; Ojeda, Eliana; Mostajo, Desireé; et al.
Highlights: The use of menopausal hormone therapy by either gynecologists themselves or their partners was assessed, as were their perceptions of the related risks. The main perceived risks relating to menopausal hormone therapy according to the gynecologists were thromboembolism and breast cancer. Gynecologists are mostly supporters of menopausal hormone therapy for themselves or their partners. Abstract: Background: Previously, the REDLINC VI study showed that the main reason for the low use of menopausal hormone therapy (MHT) was its low rate of prescription by doctors. Objective: To determine the use of MHT and perceived related risks among gynecologists. Methods: A self-administered and anonymous questionnaire was delivered to certified gynecologists in 11 Latin American countries. Results: A total of 2154 gynecologists were contacted, of whom 85.3% responded to the survey ( n  = 1837). Mean age was 48.1 ± 11.4 years; 55.5% were male, 20.3% were faculty members and 85% had a partner. Overall, 85.4% of gynecologists responded that they would use MHT if they had menopausal symptoms (81.8% in the case of female gynecologists) or prescribe it to their partner (88.2% in the case of male gynecologists; p  < 0.001). Perceived risk related to MHT use (on a scale from 0 to 10) was higher among female than among male gynecologists (4.06 ± 2.09 vs. 3.83 ± 2.11, p  < 0.02). The top two perceived reported risks were thromboembolism (women 33.6% vs. men 41.4%, p  < 0.009) and breast cancer (women 38.5% vs. men 33.9%, p  < 0.03). Overall, gynecologists reported prescribing MHT to 48.9% of their symptomatic patients (women 47.3% vs. men 50.2%, p  < 0.03) and 86.8% currently prescribed non-hormonal remedies and 83.8% alternative therapies for the management of the menopause. Gynecologists who were older and academic professionals prescribed MHT more often. Conclusion: Although this Latin American survey showed that gynecologists are mostly supporters of MHT use (for themselves or their partners), this is not necessarily reflected in their clinical practice.